Influence of pain relief management on early patents rehabilitation after total hip replacement - Kolomachenko, Vitaliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Adequate pain relief after total hip replacement can promote to decrease chronic pain, to improve muscles function and to increase joints movements. Objective: to compare different methods of pain management with scores of pain reduction and physical activity after total hip replacement. Methods: 150 patients were included into the study, patients average age (63,3 ± 12,5) years old after total hip replacement. 4 methods of anesthesia were used: general (group G , n = 25), paravertebral block in combination with caudal epidural anesthesia (group PVE, n = 25), spinal anesthesia (group S , n = 75), peripheral nerve blocks (group NB = 25). After surgery patients got a nesthesia: systemic opiods (group O , n = 75), paravertebral block (group PV, n = 50), epidural anesthesia (group E, n = 25). We estimated the time which was needed to get the next three criteria: adequate pain relief (pain intensity less than 4 according to VAS), without injections of opoids more than during 12 hours, ability to walk distance of 30 m. Results: patients from the group G took much more time (61,2 ± 23,5) hours to get three criteria after surgery comare with group PVE — (40,8 ± 17,1) hours, р = 0.0009; S — ( 48,6 ± 19,3) hours, р = 0.009; NB — (47,6 ± 15,1) hours, р = 0,02. In the group PVE we have got the best recovery result after operation. Patients of the group PV have to take significantly less time to get three criteria after surgery (38,4 ± 14,8) hours compare with group O — (56,2 ± 20,6) hours, p = 0.000001; E — (50.0 ± 17.4) hours, р = 0.003. Conclusions: prolong paravertebral anesthesia can improve postoperative course and provide better conditions for physical patient’s recovery after total hip replacement.